Energy Audit of an Industry: A Case Study of Fabrication Company - Olatunde Ajani Oyelaran; Yau Yusuf Twada; Olawale Monsur Sanusi (Aceh International Journal of Science and Technology, 2016)
Energy is one of the major inputs for the economic development of any country. In the case of the developing countries, the energy sector assumes a critical importance in view of the ever-increasing energy needs requiring huge investments to meet them. Energy audit will determine energy wastage and losses, and provide techniques and ways to minimize the losses. The payback period of the energy audit programmed for the industry was found to be 14 months. The energy consumption techniques suggested by the energy audit will not only minimize the losses but also reduce monthly electricity bill. The objective of Energy Management is to achieve and maintain optimum energy procurement and utilization, throughout the organization as to minimize energy costs and wastage without affecting production and quality. Energy Audit is the key to a systematic approach for decision-making in the area of energy management. It attempts to balance the total energy inputs with its use, and serves to identify all the energy streams in a facility.